Perlindungan Konsumen E-Commerce Dalam Kerangka Masyarakat Ekonomi Asean (MEA) - Desi Sommaliagustina; Helfira Citra; Sry Wahyuni (Jurnal Penelitian Dan Pengkajian Ilmiah Sosial Budaya, 2022)
The development of information technology with the transformation that occurs has resulted in the development of trading activities. It's not just about what is traded but also the method of trading. The trading method in question is a transaction through electronic media or what is known as electronic commerce or e-commerce. The development of e-commerce is in line with the growth of the internet. This is because e-commerce runs through the internet network. The presence of the ASEAN Economic Community (EAC) is an integration of countries in the Southeast Asian region in particular, which aims to reduce the gap between ASEAN countries in terms of economic growth. In addition to the positive impact of e-commerce trading, there are also problems, including those related to defaults that occur in the future. So that clear regulations are needed regarding dispute resolution between ASEAN member countries.